Penggunaan Elemen Visual Garis dalam Fotografi - John Felix (Humaniora, 2011)
Photography now is a science that attracts many people from those who learn it jus for hobby or those who wish to enter the industry. Since human found a way to record light and colors in photographic meaning, the challenge to produce photographic work is increase. Besides composing the light, photographers have to face a challenge on how to compose visual elements and what is the effect of using the chosen elements. This article explain how to apply one of visual elements, the line, in photographic work, as a visual element that is not only capable of giving emphasis to the main subject,but also as a visual element that can make a photograph looks comfortable to the eye of the viewer.